Investor Protection Against Invalidity of Administrative Acts: Perspective of Decision 650 K/TUN/2022 and Investment Law - Mochammad Rizky Maulana; Sang Ayu Putu Rahayu; Mayzura Kamila Sukma (Universitas Negeri Semarang, 2026)
The issuance of mining business licenses that conflict with environmental protection regulations often leads to cancellation by the court, which directly disrupts the legal certainty of investments. This article aims to examine the legal protection for investors resulting from the invalidity of administrative acts, focusing on the analysis of Supreme Court Decision Number 650 K/TUN/2022 concerning the cancellation of the Approval for the Upgrade to Operation Production Stage of PT Tambang Mas Sangihe (PT TMS). Employing a normative legal research method with statute and case approaches, this article unravels the problematic conflict between the principle of investment certainty and ecological preservation. The study reveals that PT TMS's license was annulled due to proven substantive defects, specifically violating the prohibition against massive mining on small islands as stipulated in Article 26A of the Law on the Management of Coastal Areas and Small Islands (PWP3K). While this decision represents a victory for environmental conservation, the negligence of the State Administrative Official in issuing a fundamentally flawed license has undermined the guarantee of investor protection and legal certainty under the Investment Law. From the perspective of legal doctrine, the issuance of such a juridically defective license constitutes an Unlawful Act by the Government (Onrechtmatige Overheidsdaad). Therefore, to protect the legitimate expectations of good-faith investors holding a Contract of Work, repressive legal protection through a mechanism of claiming compensation against the state becomes an essential instrument. This article recommends the necessity for strict cross-sectoral licensing synchronization to prevent similar administrative failures that could detrimentally affect the national investment climate.